A novel Heat Exchanger Network Bridge Retrofit method using the Modified Energy Transfer Diagram. (15th July 2018) - Lal, Nathan S.; Walmsley, Timothy G.; Walmsley, Michael R.W.; Atkins, Martin J.; Neale, James R.
Abstract: The aim of this paper is to develop a novel method for the retrofit of Heat Exchanger Networks based on Bridge Retrofit analysis. The method identifies Retrofit Bridges that correspond to energy saving modifications using two new proposed tools: The Heat Surplus-Deficit Table and the Modified Energy Transfer Diagram. These tools both allow the identification and quantification of Retrofit Bridges. These tools have been developed following conventional Pinch Analysis tools such as the Composite Curve and Grand Composite Curve. The connection between the conventional Heat Exchanger Network synthesis tools and the proposed retrofit tools is established to improve understanding of the method and relate it to what is currently used in both literature and industry. The method is demonstrated with a simple illustrative example and a more detail paper mill case study. The paper mill incorporates a paper machine and paper recycling plant and is co-located with a Kraft pulp mill in New Zealand. Results from the retrofit method suggest a retrofit design that will achieve an annualised profit of NZD 570, 000/y (USD 414, 000/y) with a payback of 2.4 y. Graphical abstract: Image Highlights: Developed new graphical and numerical tools for step-wise HEN retrofit. Formulated a novel retrofit method based on the new and improved tools. Applied the retrofit method to an illustrated example and Paper Plant case study.